Tracking extended mucociliary transport activity of individual deposited particles longitudinal synchrotron X-ray imaging in live mice - Donnelley, Martin (Journal of synchrotron radiation, 2014)
To assess potential therapies for respiratory diseases in which mucociliary transit (MCT) is impaired, such as cystic fibrosis and primary ciliary dyskinesia, a novel and non-invasive MCT quantification method has been developed in which the transit rate and behaviour of individual micrometre-sized deposited particles are measured in live mice using synchrotron phase-contrast X-ray imaging. Particle clearance by MCT is known to be a two-phase process that occurs over a period of minutes to days. Previous studies have assessed MCT in the fast-clearance phase, ∼20 min after marker particle dosing. The aim of this study was to non-invasively image changes in particle presence and MCT during the slow-clearance phase, and simultaneously determine whether repeat synchrotron X-ray imaging of mice was feasible over periods of 3, 9 and 25 h. All mice tolerated the repeat imaging procedure with no adverse effects. Quantitative image analysis revealed that the particle MCT rate and the number of particles present in the airway both decreased with time. This study successfully demonstrated for the first time that longitudinal synchrotron X-ray imaging studies are possible in live small animals, provided appropriate animal handling techniques are used and care is taken to reduce the delivered radiation dose